Fire in ice: two millennia of boreal forest fire history from the Greenland NEEM ice core - P. Zennaro; N. Kehrwald; J. R. McConnell; S. Schüpbach; O. J. Maselli; J. Marlon; P. Vallelonga; D. Leuenberger; R. Zangrando; A. Spolaor; M. Borrotti; E. Barbaro; et al. (Climate of the Past, 2014)
Biomass burning is a major source of greenhouse gases and influences regional to global climate. Pre-industrial fire-history records from black carbon, charcoal and other proxies provide baseline estimates of biomass burning at local to global scales spanning millennia, and are thus useful to examine the role of fire in the carbon cycle and climate system. Here we use the specific biomarker levoglucosan together with black carbon and ammonium concentrations from the North Greenland Eemian (NEEM) ice cores (77.49° N, 51.2° W; 2480 m a.s.l) over the past 2000 years to infer changes in boreal fire activity. Increases in boreal fire activity over the periods 1000–1300 CE and decreases during 700–900 CE coincide with high-latitude NH temperature changes. Levoglucosan concentrations in the NEEM ice cores peak between 1500 and 1700 CE, and most levoglucosan spikes coincide with the most extensive central and northern Asian droughts of the past millennium. Many of these multi-annual droughts are caused by Asian monsoon failures, thus suggesting a connection between low- and high-latitude climate processes. North America is a primary source of biomass burning aerosols due to its relative proximity to the Greenland Ice Cap. During major fire events, however, isotopic analyses of dust, back trajectories and links with levoglucosan peaks and regional drought reconstructions suggest that Siberia is also an important source of pyrogenic aerosols to Greenland.